LENGTH-WEIGHT RELATIONSHIP OF CYNOGLOSSUS LIDA (BLEEKER) - Seshappa, G; Chakrapani, B K (Indian Journal of Fisheries, 2011)
Studies on Length-Weight (relationships of fishes have been recognized as important aspects in fishery biology stodias. Some of- the more important Indian works in. this line ’have been mentioned by Seshappa, while giving an account of the length-weight relationships of three species of tongue soles, namely, Cynoglossus Semifasciatus (Day), C. dubius (Day) and C. bilineatus (Lacepede) at Calicut (Seshappa, in Press). Among the more recent papers in this line may be mentioned those of Hussain and AbduUa (1977), Ghatterji (1980), Soni and Kumari Maya Katbal (1979), Rita Kuimari and Balakdshnan Nair (1978), Dan and Mojumder (1978), and Victor (1978).